UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI ELASTISITAS DAN HUKUM HOOKE MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DI KELAS X TKRO-1 SMK NEGERI 2 SIGLI TAHUN PELAJARAN 2020 – 2021 - Zahra Hayati (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
This study aims to determine the increase in the learning ability of students in class X TKRO-1 physics lessons on elasticity and hooke's law in the 2020/2021 school year through the Numbered Head Together (NHT) learning model. This research was conducted at X TKRO-1SMK Negeri 2 Sigli, Pidie Regency, the research lasted for three months, from January to March 2021. The type of research used was classroom action research (PTK) which consists of 2 cycles. The research subjects were students of class X TKRO-1 SMK Negeri 2 Sigli, Pidie district, for the 2020/2021 academic year, which were 27 students. Data analysis used a comparative descriptive analysis technique by comparing the pre-cycle with the results achieved in each cycle, cycle I and cycle II. The percentage of completeness obtained in the first cycle was 66.67% with an average grade of 77.22 and increased in the second cycle to 88.89% with an average grade of 82.33. In these two cycles there was a significant change in activity and score when compared to the pre-cycle with learning completeness which only reached 51.85% and the average score was 70.00. Thus, through the application of the Numbered Heads Together (NHT) learning model, it can improve learning outcomes on elasticity and Hooke's law materials in class X TKRO-1 SMK Negeri 2 Sigli, Pidie district.Keywords: Student Learning Outcomes, Elasticity and Hooke's Law, Numbered Head Together (NHT) learning mode